Analisis Efektivitas dan Efisiensi Penyerapan Anggaran Pada BAPPELITBANGDA Kabupaten Gorontalo - Nur Ain Saba Nur Ain Saba; Yuwin Ali; Mentari Ariesta Iyonu (UMSurabaya Publishing, 2026)
This study aims to determine the effectiveness and efficiency of budget absorption at the Regional Budget Research and Development Agency (Bapelitbangda) of Gorontalo Regency during the 2020-2024 period using the effectiveness and efficiency ratio of regional spending. The method used is a mixed method sequential explanatory model. Based on the results of the study, the average effectiveness of budget absorption is 87.62%, which is considered quite effective but has not reached the minimum standard of 90%. Meanwhile, the average efficiency of budget absorption is 114.13%, categorized as inefficient, indicating that the budget is still wasteful because the value is above 100%. This is caused by several factors, namely inadequate budget planning and limited human resources, especially the number and technical competence. To address this, Bapelitbangda strives to improve the quality of planning through evaluation, strengthening and improving employee competency, and optimizing the budget management system to accelerate the process and increase the effectiveness and efficiency of budget absorption.